AIDS, the second decade - Miller, Heather G.; Turner, Charles F.; Moses, Lincoln E. (National Academy Press, 1990)
Expanding on the 1989 National Research Council volume AIDS, Sexual Behavior, and Intravenous Drug Use, this book reports on changing patterns in the distribution of cases and the results of intervention efforts under way. It focuses on two important subpopulations that are becoming more and more at risk: adolescents and women. The committee also reviews strategies to protect blood supplies and to improve the quality of surveys used in AIDS research. AIDS: The Second Decade updates trends in AIDS cases and HIV infection among the homosexual community, intravenous drug users, women, minorities, and other groups; presents an overview of a wide range of behavioral intervention strategies directed at specific groups; discusses discrimination against people with AIDS and HIV infection; and presents available data on the proportion of teenagers engaging in the behaviors that can transmit the virus and on female prostitutes and HIV infection.